2019
DOI: 10.13057/placentum.v7i1.26390
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Tingkat Pengetahuan Ibu Dengan Status Gizi Balita Di Kelurahan Wonorejo Kabupaten Karanganyar

Abstract: <p><strong>Latar belakang:</strong> Angka kematian balita (AKBA) merupakan indikator utama derajat kesehatan masyarakat. Balita yang mengalami gizi kurang pada dua tahun pertama kehidupannya, akan terjadi keterlambatan pertumbuhan fisik dan mental. Berdasarkan data dinas kesehatan tahun 2015 triwulan ketiga di Jawa Tengah angka kematian balita sebanyak 4.258 kasus, tahun 2014 sebanyak 6.486 kasus (11,54 per1.000 Kelahiran hidup). Persentase balita dengan gizi kurang ada 2,73%, gizi buruk ada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…This research shows that the mother's bad attitude is more dominant when compared to her good attitude. According to (Nurma Yuneta, Hardiningsih, & Yunita, 2019) attitude as an expression of the values held by someone. Attitudes can be formed so that the desired behavior occurs.…”
Section: Relationship Between Mother's Attitude In Giving Tempeh Brotmentioning
confidence: 99%
“…This research shows that the mother's bad attitude is more dominant when compared to her good attitude. According to (Nurma Yuneta, Hardiningsih, & Yunita, 2019) attitude as an expression of the values held by someone. Attitudes can be formed so that the desired behavior occurs.…”
Section: Relationship Between Mother's Attitude In Giving Tempeh Brotmentioning
confidence: 99%
“…It is believed that mothers with good nutritional knowledge choose the right food for themselves and their children. Noorma Yuneta said that the mother's knowledge about food is related to the mother's nutritional status, eating habits and there is a relationship between the child's knowledge about food [3]. In another study by Limoy, it was found that mothers' nutritional attitude and knowledge scores were positively related to their children's eating pattern scores [8].…”
Section: A Mother's Knowledge About the Nutritional Status Of Stunted...mentioning
confidence: 99%
“…Therefore, improving community nutrition which is focused on improving the nutrition of infants and toddlers is a start in improving the level of public health. On the other hand, malnutrition in children under five will result in the emergence of other health problems, and ultimately will have an impact on decreasing the level of public health [3]. Toddlers who experience this condition are at risk of experiencing short stature (dwarfism).…”
Section: Introductionmentioning
confidence: 99%
“…Pengetahuan dan sikap ibu terhadap gizi balita yang baik dapat membantu ibu dalam memberi makan balita, memberikan dukungan nutrisi sesuai kebutuhan balita, dan menyediakan makanan rumah tangga yang lebih baik (Chabibah et al, 2020). Tingkat pengetahuan seorang ibu merupakan kunci dalam pengelolaan rumah tangga, hal ini dapat mempengaruhi sikapnya dalam memilih bahan makanan untuk dikonsumsi keluarganya, dan juga ibu yang paham gizi akan memahami pentingnya gizi yang baik untuk kesehatan dan kesejahteraan (Eka et al, 2019 (Azrimaidaliza, 2021).…”
Section: Pendahuluanunclassified